TOLERANSI BERAGAMA MASYARAKAT MAJEMUK DALAM PERSPEKTIF KONSTITUSI - Abustan, Abustan (LPPM Universitas Bina Bangsa, 2023)
In the technological era characterized by an advances digitalization, religious issues remain important and very essential. Moreover, the Indonesian state, although various religions exist in it which is very well known for its plurality dimension. However, it remains the main concern in the country. It can be seen the arrangement / mandate in the constitution. The constitutional perspective will always be the